Development, implementation, calibration and use of practical constitutive models in finite element analysis of offshore foundations - Whyte, S (2020)
The finite element method is routinely used for the design of offshore wind turbine foundations, with complex time-consuming three-dimensional (3D) finite element analysis (FEA) typically performed to calibrate site-specific simplified macro element or one-dimensional (1D) finite models for rapid foundation sizing design calculations. The soil constitutive model used in a FEA calculation significantly influences the predicted foundation response. Therefore, given the uptake by industry of FEA for offshore wind turbine foundation design, it is important that practical advanced constitutive models are available which can be demonstrated to work robustly and accurately as design tools.